2018
DOI: 10.21315/mjms2018.25.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Amygdalin on Endoplasmic Reticulum (ER) Stress Induced Hepatic Steatosis in Mice

Abstract: Conclusion: Amygdalin improved the ALT, AST, and lipid serum levels after the TM challenge; however, it could not attenuate hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It can alleviate the inhibition of colitis [72], reduce the production of TNF-α and have a significant protective effect on hepatocytes [73]. It has been reported that amygdalin has obvious anti-inflammatory activity by reducing the secretion of TNF-α [74], effectively alleviating hepatic steatosis caused by endoplasmic reticulum stress. The above metabolomic analysis results show that AAM intervention can obviously improve alcoholic liver injury in mice with excessive alcohol consumption by regulating lipid metabolism, oxidative stress and inflammatory related metabolites.…”
Section: Effects Of Aam On the Liver Metabolomic Profiling In Model Micementioning
confidence: 99%
“…It can alleviate the inhibition of colitis [72], reduce the production of TNF-α and have a significant protective effect on hepatocytes [73]. It has been reported that amygdalin has obvious anti-inflammatory activity by reducing the secretion of TNF-α [74], effectively alleviating hepatic steatosis caused by endoplasmic reticulum stress. The above metabolomic analysis results show that AAM intervention can obviously improve alcoholic liver injury in mice with excessive alcohol consumption by regulating lipid metabolism, oxidative stress and inflammatory related metabolites.…”
Section: Effects Of Aam On the Liver Metabolomic Profiling In Model Micementioning
confidence: 99%
“… 62 In special circumstances, such as pharmacological stimuli, oxidative stress, viral infections and dietary demands, ER homeostasis can disrupt and create an ER stress phenomenon 63 that causes abnormalities in insulin action, inflammatory responses, lipoprotein B100 degradation and hepatic lipogenesis. 64 Three ER transmembrane sensors, inositol-requiring protein 1, protein kinase-like ER kinase and activating transcription factor 6, are activated by the glucose-regulated protein 78 required for folding of proteins in the ER. Tunicamycin, cow milk casein or oxidative stress induce acute ER stress, 65 , 66 while overfeeding of fatty acids, cholesterol and fructose, due to the produced obesity and insulin resistance, induce chronic ER stress that is not fully restored.…”
Section: Srebps In Liver Diseasementioning
confidence: 99%
“…Accumulation of several hepatic lipids has been observed in the livers of mice treated with tunicamycin (a classic ERS inducer), which can induce phosphorylation of PERK, increase the expression levels of Chop and Grp78 and inhibit the expression of ApoB100 [50]. As shown in a study by Shen C et al, palmitic acid is likely to cause hepatic lipotoxicity by activating the TLR4-IRE1α pathway.…”
Section: Activation Of Er Stress In Patients With Nafldmentioning
confidence: 99%
“…During ERS, accumulation of excess misfolded proteins due to the limited compensatory capacity of the ER to clear misfolded proteins can activate autophagy [55]. Activation of the PERK-eIF2α-ATF4 pathway and the IRE1-JNK pathway promotes autophagy, which ensures, to some extent, normal energy metabolism and immune responses in cells, ultimately promoting cell survival [50]. Autophagy reduces the level of ERS mainly by removing the ER membrane portion containing the UPR sensor and clearing abnormal proteins in the ER [55].…”
Section: Activation Of Er Stress In Patients With Nafldmentioning
confidence: 99%